Business Rates : Consultation on proposals on the design and implementation of the locally administered Business Rates Relief Scheme.: Consultation on proposals on the design and implementation of the locally administered Business Rates Relief Scheme. (March 2017) - Great Britain., Department for Communities and Local Government
No abstract available